Characterization of TRAF2 in Nile tilapia: Expression profiles and the role in decreasing NF-κB pathway. Issue 122 (March 2022) - Hu, Huiling; Wang, Zhiwen; Yu, Dapeng; Xia, Liqun; Chen, Wenjie; Long, Meng; Fan, Huimin; Xia, Hongli; Lu, Yishan
Abstract: Mammals TRAF2 played a dual role in several immune signaling transduction processes. In this study, TRAF2 was cloned from Nile tilapia, Oreochromis niloticus, which named OnTRAF2 . The open reading frame was 1797 bp, encoding 598 amino acids. Amino acid alignment and phylogenetic analysis indicated that OnTRAF2 showed relatively low identify with other teleost TRAF2 proteins, with the exception of TRAF2s from Epinephelus coioides . In healthy tilapia, OnTRAF2 was expressed widely in all the examined tissues, which had highest expression level in the brain. After Streptococcus agalactiae infection, the expression level of OnTRAF2 was increased significantly at different times in several organs, implying that OnTRAF2 may be involved in host defense against S. agalactiae infection. The result of subcellular localization showed that OnTRAF2 presented in cytoplasm and nucleus of HEK293T cells. Additionally, overexpression of OnTRAF2 significantly decreased the transcriptional activity of the NF-κB reporter in HEK293T cells, yeast two-hybrid results revealed that OnTRAF2 had no interaction with E3 ubiquitin ligase OnNEDD4. These results indicated that OnTRAF2 played important function during bacterial infection, and negatively mediated the immune signaling transduction in Nile tilapia, while the mechanism need further study. Highlights: 1. Tumor necrosis factor receptor-associated factor 2(OnTRAF2) homologue was cloned and characterized from Nile tilapia, Oreochromis niloticus. 2. OnTRAF2 was expressed widely in all detected tissues. After Streptococcus agalactiae stimulation, OnTRAF2 was significantly up-regulated in several tissues. 3. OnTRAF2 presented in cytoplasm and nucleus of HEK293T cells, and played a negative regulator in the activation of the NF-κB reporter. 4. OnTRAF2 had no interaction with E3 ubiquitin ligase OnNEDD4 through yeast two-hybrid assay.